(SMAKYVXFUJVJ VXJP FQFNLQJ XRY NRDRY(B, (SXJV ROLNLAV MAL ELAXAUA[FV XJV AUKU]VJVs ((SAyxrfmervjs (SVynnrgc(Slmr(B,s, 1985)
(SSUAMXLMA (B2 (SVYPFEULRY XRY SAPFNNJPLRY VYNNRDRY FLELM]P VXLV ELAXAUA[FV XRY NRDRYs
(SSUAMXLMA (B2 (SVYPFEULRY XRY SAPFNNJPLRY VYNNRDRY FLELM]P VXLV ELAXAUA[FV XRY NRDRYs